2015
DOI: 10.18632/oncotarget.4485
|View full text |Cite
|
Sign up to set email alerts
|

Combination of antibodies directed against different ErbB3 surface epitopes prevents the establishment of resistance to BRAF/MEK inhibitors in melanoma

Abstract: Patients with metastatic melanoma bearing V600 mutations in BRAF oncogene clinically benefit from the treatment with BRAF inhibitors alone or in combination with MEK inhibitors. However, a limitation to such treatment is the occurrence of resistance. Tackling the adaptive changes helping cells survive from drug treatment may offer new therapeutic opportunities. Very recently the ErbB3 receptor has been shown to act as a central node promoting survival of BRAF mutated melanoma. In this paper we first demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 53 publications
3
36
0
Order By: Relevance
“…Our data is supported by previous studies showing that both ERBB3 expression and phosphorylation can be elevated after MAPK inhibitor treatment [1520]. Hyper-activation of the PI3K/AKT pathway due to increased NRG1-beta/ERBB3 pathway signaling has previously been reported to be responsible for acquired drug resistance in BRAFV600 melanomas [15, 17]. However, also low MITF/AXL and MITF/EGFR ratios have been suggested to be involved in early resistance to vemurafenib in a subset of melanomas [12, 13].…”
Section: Discussionsupporting
confidence: 91%
“…Our data is supported by previous studies showing that both ERBB3 expression and phosphorylation can be elevated after MAPK inhibitor treatment [1520]. Hyper-activation of the PI3K/AKT pathway due to increased NRG1-beta/ERBB3 pathway signaling has previously been reported to be responsible for acquired drug resistance in BRAFV600 melanomas [15, 17]. However, also low MITF/AXL and MITF/EGFR ratios have been suggested to be involved in early resistance to vemurafenib in a subset of melanomas [12, 13].…”
Section: Discussionsupporting
confidence: 91%
“…S1). Finally, we decided to measure miR-579-3p expression in three BRAF mutated melanoma cell lines resistant to vemurafenib recently derived in our laboratory (18). miR-579-3p expression was strongly down-regulated in resistant M14, A375 (both BRAF V600E), and WM266 (BRAF V600D) compared with wild-type cells (Fig.…”
Section: Significancementioning
confidence: 99%
“…We and others, for example, have demonstrated that the ErbB3 receptor is a key player in the development of resistance to therapies in melanoma (16,17). This receptor is involved in the activation of an early feedback survival loop upon melanoma cell exposure to BRAF and MEK inhibitors, and monoclonal antibodies directed against ErbB3 act synergistically in combination with BRAF and MEK inhibitors to impair the development of drug resistance (16,18). In this paper, to investigate the possible role of the epigenetic or posttranscriptional changes in the establishment of drug resistance, we demonstrate that miRNAs could be novel and important effectors.…”
mentioning
confidence: 99%
“…Hyperactivation of ERBB3 receptor through phosporylation has been observed as an early feedback survival loop both in vitro and in vivo in response to RAF/MEK inhibition. This activation can be abrogated by anti-ERBB3 antibodies preventing the establishment of resistance to BRAF/MEK inhibitors in melanomas [23]. The feedback survival loop is promoted by increased autocrine production of EGFR ligand neuregulin, whose increased level of gene expression has been observed after BRAFi treatment in several cell lines and its secretion occurs shortly after melanoma cell exposure to BRAFi [24].…”
Section: Molecular and Immune Advancesmentioning
confidence: 99%